Increased Osteopontin Expression in Dendritic Cells Amplifies IL-17 Production by CD4+ T Cells in Experimental Autoimmune Encephalomyelitis and in Multiple Sclerosis - Murugaiyan, Gopal; Mittal, Akanksha; Weiner, Howard L (The Journal of immunology (1950), 2008)
Osteopontin (Opn) is a broadly expressed pleiotropic cytokine, and has been shown to play an important role in various autoimmune diseases, including multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE). It is reported that Opn exacerbates EAE by skewing T cell differentiation toward IFN-γ-producing Th1 cells. Opn expression in dendritic cells (DCs) and its role in IL-17 induction from T cells during EAE or MS are unknown. We found that during EAE, Opn expression is elevated in DCs both in the periphery and in the CNS. There was increased expression of Opn receptor on T cells, and Opn induced IL-17 production by CD4+ T cells via the β3 integrin receptor and Opn inhibited IL-10 production via the CD44 receptor. Furthermore, anti-Opn treatment reduced clinical severity of EAE by reducing IL-17 production. Anti-Opn was also effective in reducing clinical severity of EAE when given after the appearance of clinical symptoms. Analogous to EAE, in subjects with MS, we found increased expression of Opn in DCs and increased expression of the Opn receptors CD44, β3, and αv on T cells. Furthermore, Opn-stimulated CD4+ T cells from MS patients produced significantly higher amounts of IL-17. Our results demonstrate a role for DC-produced Opn both in EAE and MS that is linked to the production of IL-17.